ChemInform Abstract: Highly Efficient Synthesis of Tetrasubstituted 2, 3‐Dihydropyrans by Three‐Component "One‐Pot" Reaction. Issue 35 (August 2016) - Li, Chao; Cai, Liang‐Zhen; Liu, Xiao‐Dong; Zhu, Shi‐Zheng; Xing, Chun‐Hui; Lu, Long
Abstract: β‐Keto perfluoroalkanesulfones react with aldehydes and vinyl ethers to produce dihydropyran products as cis‐ and trans‐diastereomeric mixtures.